2012
DOI: 10.1111/jth.12000
|View full text |Cite
|
Sign up to set email alerts
|

Population pharmacokinetic modeling for dose setting of nonacog beta pegol (N9‐GP), a glycoPEGylated recombinant factor IX

Abstract: To cite this article: Collins PW, Møss J, Knobe K, Groth A, Colberg T, Watson E. Population pharmacokinetic modeling for dose setting of nonacog beta pegol (N9-GP), a glycoPEGylated recombinant factor IX. J Thromb Haemost 2012; 10: 2305-12.Summary. Background: nonacog beta pegol (N9-GP) is a glycoPEGylated recombinant factor IX (rFIX) molecule with a prolonged half-life. Objectives: To provide information on potential dose regimens for N9-GP for phase 3 pivotal and surgery trials. Methods: A population pharmac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 30 publications
4
51
0
Order By: Relevance
“…This observed high bleed protection with N9‐GP 40 IU/kg once‐weekly prophylaxis may improve long‐term treatment outcomes by increasing physical activity, decreasing the number of injections/treatment burden, and reducing factor consumption. Given that most haemophilia B patients follow a twice‐weekly regimen, the annual number of injections could be reduced by approximately half, while maintaining potentially better protection, compared with current unmodified products . Resolution of existing target joints in adolescents and adults was demonstrated in this pooled analysis, and aligns with the results of previous analyses of EHL products for long‐term prophylaxis .…”
Section: Discussionsupporting
confidence: 74%
“…This observed high bleed protection with N9‐GP 40 IU/kg once‐weekly prophylaxis may improve long‐term treatment outcomes by increasing physical activity, decreasing the number of injections/treatment burden, and reducing factor consumption. Given that most haemophilia B patients follow a twice‐weekly regimen, the annual number of injections could be reduced by approximately half, while maintaining potentially better protection, compared with current unmodified products . Resolution of existing target joints in adolescents and adults was demonstrated in this pooled analysis, and aligns with the results of previous analyses of EHL products for long‐term prophylaxis .…”
Section: Discussionsupporting
confidence: 74%
“…OCM resulted definitely less accurate than TCM because of its higher SSR. TCM seems to fit better the PK data of rFIX, as also recently reported . We would like to recommend that the choice of the best fitting compartment method should be based on SSR.…”
Section: Discussionmentioning
confidence: 99%
“…The 10 IU/kg and 40 IU/kg once-weekly prophylactic treatment regimens were based on the modeling of pharmacokinetic data from the first human dose trial with nonacog beta pegol in patients with hemophilia B. 8,9 At screening, the patient and investigator decided whether prophylaxis or an on-demand treatment regimen would be used. Patients who chose prophylaxis were randomly assigned 1:1 in a blinded fashion to 1 of the 2 prophylaxis groups.…”
Section: Trial Designmentioning
confidence: 99%
“…The activation peptide with the PEG is cleaved off during the coagulation process to leave native activated FIX. 7,8 Pharmacokinetic data from the first human dose trial demonstrated a 5-fold increase in terminal half-life compared with commercially available standard FIX products, offering the possibility of once-weekly prophylaxis. 9 The aim of this prospective, multinational, randomized, singleblind, phase 3 clinical trial was to evaluate the safety (including immunogenicity), efficacy, and pharmacokinetics of nonacog beta pegol in previously treated patients with hemophilia B.…”
Section: Introductionmentioning
confidence: 99%